Canal do preço dos ativos no Brasil: caso das LFTs - Medeiros, Felipe; Araújo, Eliane (Revista de Economia do Centro-Oeste, 2015)
One explanation for that even after inflation stabilization after the “Plano Real” Brazil still maintains one of the highest real interest rates in the world, formed on the assumption that monetary policy in the country may not work properly. Therefore, this study aims to investigate the Asset Price Channel, as shown in other studies as an essential tool for monetary policy, but may be stopping or even reversing their desired effects when is contaminated by an interference caused by Treasury bills. To complete this task, the work will have a chapter that will present the importance and functioning of the LFTs as the elements of monetary policy contamination, and following an empirical study based on structural VAR models to test the hypothesis.